Study of Periphyton on Glass Substrates in Sago River Pekanbaru - Prian Mintaito Simangunsong; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Periphyton is a group of microorganism that grow in some natural substrates such as rock, wood, plants and aquatic animals.A research aims to understand the type and abundance of periphyton in the Sago River has been carried out in April-May 2015. Samples were taken from three station, once/ week for a 4 weeks period. Type of periphyton was identified based on Prescot (1974), and Yunfang (1995). Result shown that there are 39 types of periphyton and they are belonged to 8 classes, namely Bacillariophyceae (13 species), benthic Crustacean (1 species), Chlorophyceae (6 species), Cyanophyceae (8species), Cryptophyceae (3species), Dinophyceae (4species), Euglenophyceae (2 species) and Xanthophyceae (2 species).The abudance of periphyton in the all station Sago River is significantly different, there were S1 (7,533cells/cm2), S2 (10,206cells /cm2), and S3 (13,277cells /cm2). The abundance of periphyton in the Sago River in general was around 7,533– 13,277 cells /cm2.Keywords: Sago River, Periphyton, Glass Substrates